In the Absence of Sexual Desire: we Activate the Permission to be Presents - Barrozo, Elizabeth Viviana (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2016)
In this age, talking about sexuality is to get communicated, and sexuality is communication. The absence of sexual desire requires multiple approaches but, above all, it needs the activation of permits: to feel, enjoy, live, love and be loved, experiences linked to this present. We offer, as an approach to achieve this objective, a valuable tool that we call: “Transactional Pantomime”, therapy link art and science, in a leading meeting way, at the highest point of communication: the intimacy.